Funkcional'naja podgotovlennost' sportsmenov igrovych vidov sporta s ucetom ich igrovogo amplua - Iordanskaja, F. A. (Vestnik sportivnoj nauki; Sports science bulletin, 2018)
Diagnostics of fitness in athletes of different age groups revealed different levels of preparedness and tension in adaptation systems to general and special test loads. Preparation on the precompetitive stage and competitive activity also cause pronounced differences in health indicators of junior and adult athletes. The results of our research indicate the need for the development of individual training programs for juniors taking into account age-appropriate development of the body and identified weak links of the fitness.